Implementing professional learning community in rural Malaysian primary schools: exploring teacher feedback. (2nd April 2020) - Tahir, Lokman Mohd.; Musah, Mohammed Borhandden
This study investigates whether teachers in rural primary schools are satisfied with the implementation of professional learning community (PLC) and with its practicality and suitability in the rural settings. Using a pragmatic mixed-method, we obtained the viewpoints of 338 rural primary teachers on the effectiveness of PLC implementation within their schools. Furthermore, eight rural primary teachers were interviewed to explore the benefits and challenges of PLC in the sampled schools. The findings reveal that rural primary teachers feel contented with the PLC implementation within their schools. They note the benefits of the program as part of their effective professional development. Other benefits, such as the establishment of teachers' teamwork culture and the ability of the program to support teachers' learning process, were also addressed. PLC was also described as an effective knowledge-sharing platform. The findings also disclose some challenges such as lack of time, negative attitudes of teachers and financial constraints that impeded the effective execution of PLC at rural primary schools. The findings suggest improvements to the practices of rural primary schools.